TRANSFORMASI TEKNOLOGI KOMUNIKASI DAKWAH PESANTREN DARUSSALAM MENUJU ERA DIGITALISASI (5.0) - Fathurrahman, Afif; maskur (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2024)
Digitalization of communication technology in the digital age (5.0) has a huge role in changing or shifting the concept of public communication. There is no exception to the concept of the communication of the dakwah in the Darussalam Blokagung training as the basis of the Dakwah in eastern Java region in particular Banyuwangi. Digital change opens up new opportunities for preachers in calling for religious scholarship, but in addition to the vastness of opportunities that are emerging, the challenges that arise cannot be ignored. The study examines the process of transformation of communications technology of Darussalam practitioners along with the development of communication technology in the era of digitalization (5.0), besides, the researchers also look for the obstacles experienced by practisees during practising using digital media. In this study, the author uses a qualitative research method approach in his research. Data collection uses observations, in-depth interviews and documentation. The results of the research show that the transformation of the technology of communication is very important to be conceived, because the practitioner must preserve its existence as the center of the teaching then the change of the concept of teaching itself is very necessary to be done. It doesn't mean abandoning the old methods, but it's more to innovate looking for easier methods of religious learning.